Botanical and geotechnical characteristics of blanket peat at three Irish bogflows. Issue 1 (18th October 2018) - Foteu Madio, Eliane S; Dykes, Alan P
Abstract : The potential importance of botanical controls on the properties and behaviour of blanket peat involved in peat landslides was identified almost twenty years ago. During 2010–2012, investigations of the blanket peat at three bogflows in north-west Ireland were done with the aim of establishing some form of relationship between botanical or palaeoecological characteristics and standard physical and geotechnical properties, assuming the latter to be meaningful but recognising that this may not be the case. In situ measurements and investigations at all three sites were followed by extensive laboratory characterisation of small core, block and monolith samples. The botanical composition of the peat could not be fully determined due to the high degree of decomposition. However, analysis of macrofossils allowed distinct depth-related patterns of several key botanical indicators to be determined. In particular, the monocotyledon fragments, dominated by Eriophorum vaginatum, showed distinct and potentially useful distributions throughout the peat profiles. Overall results showed that the basal peat at one site was discernibly different from the other two sites, having fewer monocotyledons, fewer fibres, higher dry bulk density and higher saturated hydraulic conductivity. This approach therefore offers a potential basis for developing a means of assessing peat mass characteristics from small auger samples.